Next-generation sequencing analysis of cholangiocarcinoma identifies distinct IDH1-mutated clusters. (November 2022) - Rimini, Margherita; Loi, Eleonora; Fabregat-Franco, Carles; Burgio, Valentina; Lonardi, Sara; Niger, Monica; Scartozzi, Mario; Raposelli, Ilario G.; Aprile, Giuseppe; Ratti, Francesca; Pedica, Federica; Verdaguer, Helena; et al.
Abstract: Background: IDH1 -mutated intrahepatic cholangiocarcinomas ( IDH1 m iCCAs) could be treated with anti-IDH1 drugs, although the high heterogeneity in this class of tumours could limit treatment efficacy. Methods: We selected 125 IDH1 m iCCAs that were treated as resectable, locally advanced, or metastatic and were screened by the NGS-based FoundationOne gene panel. We conducted a mutation-based clustering of tumours and survival analysis. Results: Three main clusters were identified. The most altered pathways in cluster 1 were cell cycle and apoptosis, RTK/RAS, PI3K, and chromatin modification. Of note, CDKN2A/2B were mutated in 41/44 patients of this cluster. In cluster 2, the most affected pathways were as follows: Chromatin modification, DNA damage control, PI3K, and RTK/RAS. In this cluster, the most frequently mutated genes were ARID1A and PBRM1 . The most altered pathways in cluster 3 were as follows: Cell cycle and apoptosis, DNA damage control, TP53, and chromatin modification. Importantly, TP53 was mutated only in cluster 3 patients. In the cohort of patients treated with surgery, cluster 2 showed statistically significant better disease-free survival (DFS) and overall survival (OS) compared with patients in cluster 3 and cluster 1 (p = 0.0014 and p = 0.0003, respectively). In the advanced setting, cluster 2 experienced a statistically significant better PFS (p = 0.0012), a tendency toward a better OS from first-line treatment, and a better OS from first-line progression compared with patients in cluster 1 and cluster 3 (p = 0.0017). We proposed an easy-to-use algorithm able to stratify patients in the three clusters on the basis of the genomic profile. Conclusion: We highlighted three different mutation-based clusters with prognostic significance in a cohort of IDH1 m iCCAs. Highlights: IDH1-mutated cholangiocarcinomas are a heterogeneous group of neoplasia. We performed a mutation-based clustering on a sample of 125 IDH1-mutated iCCAs. Three main clusters have been highlighted, and an easy-to-use algorithm has been proposed. From the survival analysis, the three clusters resulted to have a prognostic role.